The impact of play-based learning on early mathematical communication skills in children aged 5–6 years - Priyanti, Nita; Adrian, Teddy; Warmansyah, Jhoni; Amalina (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: Early mathematics learning in early childhood education often emphasizes procedural skills such as counting and number recognition, while mathematical communication receives less attention. Consequently, children have limited opportunities to express, represent, and interpret mathematical ideas meaningfully. This study aimed to examine the impact of play-based learning on early mathematical communication skills among children aged 5–6 years.Method: A quantitative approach employing a quasi-experimental pretest–posttest control group design was used. The participants consisted of 32 children aged 5–6 years enrolled at Al Azkar Kindergarten, Pamulang, Indonesia. Data were collected using an observational instrument based on the learning trajectories framework and analyzed using Analysis of Covariance (ANCOVA) to determine the effect of the intervention while controlling for initial ability.Findings: The results revealed a significant effect of play-based learning on early mathematical communication skills. Children in the experimental group demonstrated significantly higher posttest scores than those in the control group after controlling for pretest performance (p < .001). The intervention produced a very large effect (η²p = .886), indicating substantial improvement in children’s ability to express, represent, and interpret mathematical ideas through verbal, representational, visual, and symbolic forms of communication.Significance: This study provides empirical evidence that play-based learning is an effective approach for fostering multidimensional mathematical communication in early childhood. The findings contribute to the growing literature on early mathematics education by positioning mathematical communication as a central developmental outcome and highlighting the role of play in supporting meaningful mathematical learning.